HUBUNGAN KARAKTERISTIK PETANI DENGAN EFEKTIVITAS KOMUNIKASI PENYULUHAN PERTANIAN DALAM PROGRAM SL-PTT (Kasus Kelompok Tani di Kecamatan Kerkap Kabupaten Bengkulu Utara) - Sri Narti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
Elucidator role on SL-PTT program is really important. As spreading the information in elucidation activity was directly doing to the farmers. The elucidator prosecuted not only to be able to spread the information about SL-PTT but it should helps the farmer to analyze the happening situation, enhance their knowledge about SL-PTT, and develop their insight toward the problem too. The purposes of this research are to describe about communication effectiveness between elucidator with the farmer and acknowledge how far the relationship between farmer characteristic and communication effectiveness on SL-PTT program. This research use quantitative-descriptive with the population of farmworker group in Kerkap Subdistrict, Bengkulu Utara Regency. The sample-taking of 90 people from farmworker group doing by using Slovin’s formula. Determine the amount sample per farmworker group using Proportionale Random Sampling and Accidental Sampling used for choosing sample per each group of farmworker. Data-gathering was doing by gone round a set of question toward the respondent to be answered through questionnaire. And the data analysis is using correlation Chi-Square, a correlation test that has fuction to observe relation between two variable. The result of this research shows that the communication effectiveness of farming elucidation on SL-PTT program in Kerkap, Bengkulu Utara, rated with effective enough. Age variable is significant related with communication effectiveness between elucidator and farmer. Education level is significant related with communication effectiveness between elucidator and farmer. Landmass is significant related with communication effectiveness between elucidator and farmer. Media consumption is significant related with communication effectiveness between elucidator and farmer. Too, the frequency to join elucidation is significant related with communication effectiveness between elucidator and farmer. And the most dominant farmer’s characteristic that related to communication efectiveness is the farmer education level and frequency following the guidance.